Hydroalumination of seleno acetylenes: a versatile generation and reactions of alpha-aluminate vinyl selenide intermediates in the highly regio and stereoselective synthesis of telluro(seleno)ketene acetals - Guerrero, Palimclo G. [UNESP]; Dabdoub, Miguel J.; Baroni, Adriano C. M. (Pergamon-Elsevier B.V. Ltd, 2008)
The hydroalumination of butylseleno acetylenes with DIBAL-H followed by addition of n-butyllithium generated in situ the (Z)-butylseleno vinyl alanates intermediates which were captured with C(4)H(9)TeBr furnishing the (E)-telluro(seleno)ketene acetals exclusively. The isomers with opposite stereochemistry (Z)-telluro(seleno)ketene acetals were obtained by the reduction of phenylseleno acetylenes with lithium di-(isobutyl)-n-butyl aluminate hydride (Zweifel's reagent) followed by reaction of (E)-phenylseleno vinyl alanates intermediates with C(4)H(9)TeBr. (c) 2008 Elsevier Ltd. All rights reserved.